2022
DOI: 10.3390/plants11020190
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Changes and Its Associated Genes in Mulberry (Morus alba L.) Yu-711 Response to Drought Stress Using MethylRAD Sequencing

Abstract: Drought stress remains one of the most detrimental environmental cues affecting plant growth and survival. In this work, the DNA methylome changes in mulberry leaves under drought stress (EG) and control (CK) and their impact on gene regulation were investigated by MethylRAD sequencing. The results show 138,464 (37.37%) and 56,241 (28.81%) methylation at the CG and CWG sites (W = A or T), respectively, in the mulberry genome between drought stress and control. The distribution of the methylome was prevalent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Correlation analysis has shown that DNA methylation has multiple effects on gene expression under drought stress, indicating that it directly or indirectly affects gene ex-pression through multiple regulatory pathways. Drought-tolerant plants were found to have a more stable methylome under drought conditions, with differentially methylated regions (DMRs)-related genes mainly related to the stress response, programmed cell death, and other pathways in rice (Oryza sativa L.) [26], mulberry (Morus alba L.) [27], mungbean (Vigna radiata L.) [28], and maize (Zea mays L.) [29]. For example, an in-silico genome-wide DNA methylation (5mC) analysis was performed in rice (Oryza sativa cv.…”
Section: Dna Methylation and Drought Stressmentioning
confidence: 99%
“…Correlation analysis has shown that DNA methylation has multiple effects on gene expression under drought stress, indicating that it directly or indirectly affects gene ex-pression through multiple regulatory pathways. Drought-tolerant plants were found to have a more stable methylome under drought conditions, with differentially methylated regions (DMRs)-related genes mainly related to the stress response, programmed cell death, and other pathways in rice (Oryza sativa L.) [26], mulberry (Morus alba L.) [27], mungbean (Vigna radiata L.) [28], and maize (Zea mays L.) [29]. For example, an in-silico genome-wide DNA methylation (5mC) analysis was performed in rice (Oryza sativa cv.…”
Section: Dna Methylation and Drought Stressmentioning
confidence: 99%
“…The MSAP and WGBS techniques are frequently used to investigate the methylation status involved in regulating gene expression in plants under environmental stresses. Epigenetic research has revealed that drought-tolerant plants exhibited a more stable methylome, with differentially methylated regions (DMRs) linking genes primarily involved in the programmed cell death and stress response in mulberry ( Ackah et al., 2022 ), mungbean ( Zhao et al., 2022 ) and rice ( Wang et al., 2016 ). Likewise, the differentially methylated epiloci (DME) identified 12 stress-related genes in rice genotypes under high temperature treatment ( Li et al., 2022b ).…”
Section: Multi-omics Techniques Accelerate the Genetic Dissection Of ...mentioning
confidence: 99%
“…Beta-glucosidases have very diverse roles in plants: cell wall lignification and degradation, activation of several phytohormones and generation of signal molecules (Morant et al ., 2008). A role for this enzyme in DS responses has also been suggested in Arabidopsis (Han et al ., 2012) and mulberry (Ackah et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%